Comparison between MCNP5, Geant4 and experimental data for gamma rays attenuation of PbO–BaO–B2O3 glasses - M. Almatari; Shams A.M. Issa; M.G. Dong; M.I. Sayyed; R. Ayad (Heliyon, 2019)
Monte Carlo simulations, MCNP5 and Geant4 codes were developed to investigate radiation shielding properties of xPbO–(50-x) BaO–50B2O3 (where 5 ≤ x ≤ 45 mol%) consider to be glass systems. The mass attenuation coefficients were evaluated for different PbO concentration in the glass samples for varies photon energies of 0.356, 0.662, 1.173 and 1.332 MeV. The obtained mass attenuation coefficient values used to calculate half-value layer, effective atomic number, and electron density. The simulation parameters were compared with experimental data. Results show that the simulation results of mass attenuation coefficients for all PbO concentrations were generally in good agreement with experimental results, however, mass attenuation coefficient values calculated using Geant4 were slightly lower than MCNP5 and experimental data on the low energy of 0.356 MeV. The results obtained from MCNP5 and Geant4 codes might be able to assessment mass attenuation for different glass systems. Furthermore, gamma ray, fast neutron and charged particle interaction for the glass systems were studied using buildup factors, fast neutron removal cross sections and ranges respectively.